Studi Kritis terhadap Kata Elohim: Suatu Tinjauan Kristis terhadap kata Elohim sebagai Sesembahan Bangsa Israel - Sihombing, Bernike (STT IKSM SANTOSA ASIH, 2024)
Abstract: The word Elohim is very well known among Jews, Christians also among non-Jews or nonChristians. In the three beliefs referred to above, the word elohim is very often used as a pronoun to those who are considered omnipotent according to their respective religious beliefs. Does the elohim in question have a relationship between the elohim known to the Israelites and the elohim known to Christians and idol worshipers, or is it only a similarity in name, or is it the same person but different actions. So to find out, it is necessary to do a study as a lesson to be used as a criticism of the word elohim to equip teachers in Christian Religious Education or church youth, so that they are equipped to understand what Elohim meansin the context of the belief as referred to above. Abstrak: Kata Elohim sangat terkenal di kalangan orang Yahudi, Kristen juga di kalangan non Yahudi atau non-Kristen. Dalam ketiga kepercayaan tersebut di atas, kata elohim sangat sering digunakan sebagai kata ganti orang yang dianggap maha kuasa menurut keyakinan agamanya masing-masing. Apakah elohim yang dimaksud ada hubungan antara elohim yang dikenal orang Israel dengan elohim yang dikenal orang Kristen dan penyembah berhala, atau hanya kesamaan nama, atau orang yang sama tetapi tindakan yang berbeda. Maka untuk mengetahuinya perlu dilakukan kajian sebagai pelajaran untuk dijadikan sebagai kritik terhadap kata elohim untuk membekali para guru di Pendidikan Agama Kristen atau pemuda gereja, agar mereka dibekali untuk memahami apa yang dimaksud dengan Elohim dalam konteks kepercayaan sebagaimana tersebut di atas.